Phrenic nerve stimulation to treat patients with central sleep apnoea and heart failure. (10th October 2018) - Costanzo, Maria Rosa; Ponikowski, Piotr; Coats, Andrew; Javaheri, Shahrokh; Augostini, Ralph; Goldberg, Lee R.; Holcomb, Richard; Kao, Andrew; Khayat, Rami N.; Oldenburg, Olaf; Stellbrink, Christoph; McKane, Scott; et al.
Abstract : Aims: The presence of central sleep apnoea (CSA) is associated with poor prognosis in patients with heart failure (HF). The aim of this analysis was to evaluate if using phrenic nerve stimulation to treat CSA in patients with CSA and HF was associated with changes in HF‐specific metrics. Methods and results: All patients randomized in therem edē System Pivotal Trial and identified at baseline with HF were included ( n = 96). Effectiveness data from treatment and former control groups were pooled based on months since therapy activation. Changes from baseline to 6 and 12 months in sleep metrics, Epworth Sleepiness Scale, patient global assessment health‐related quality of life, Minnesota Living with Heart Failure Questionnaire (MLHFQ), and echocardiographic parameters are reported. HF hospitalization, cardiovascular death, and the composite of HF hospitalization or cardiovascular death within 6 months are reported by the original randomized group assignment for safety assessment. Sleep metrics and quality of life improved from baseline to 6 and 12 months. At 12 months, MLHFQ scores changed by –6.8 ± 20.0 ( P = 0.005). The 6‐month rate of HF hospitalization was 4.7% in treatment patients (standard error = 3.3) and 17.0% in control patients (standard error = 5.5) ( P = 0.065). Reported adverse events were as expected for a transvenous implantable system. Conclusions: Phrenic nerve stimulation reduces CSA severity in patients with HF. In parallel, this CSA treatment was associated with benefits on HF quality of life.